Internalisation of Ahlussunnah wal Jama'ah values among Umrah Pilgrims from the Perspective of Islamic Religious Education - Moh. Affan; Ahmad Shauqi Alaika Rohman; Siswanto; Mona Novita (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
This study is motivated by the importance of strengthening moderate religious understanding amid the increasing complexity of contemporary religious practices, particularly among umrah pilgrims with diverse backgrounds. In the context of Islamic Religious Education, the internalisation of Ahlussunnah wal Jama’ah (Aswaja) values plays a crucial role in shaping balanced, tolerant, and inclusive religious character. Previous studies have mostly focused on the ritual and managerial aspects of umrah, while limited attention has been given to the process of internalising Aswaja values through non-formal Islamic education among pilgrims. Therefore, this study aims to analyse the process, strategies, and implications of internalising Aswaja values among umrah pilgrims. This research employs a qualitative approach using a case study design conducted at three Umrah travel agencies. Data were collected through interviews, observations, and documentation, and analysed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the internalisation of Aswaja values occurs systematically through pre-departure manasik (ritual guidance), mentoring during the pilgrimage in the holy land, and post-umrah reinforcement, integrating cognitive, affective, and psychomotor aspects. The strategies applied include persuasive lectures, interactive dialogue, role modelling, habituation, and contextual experiential learning. The implications of this study indicate a transformation in pilgrims’ religious understanding and practices toward being more moderate, tolerant, and inclusive. Theoretically, this study contributes to the discourse of Islamic Religious Education by emphasising that umrah travel agencies function not only as service providers but also as agents of non-formal Islamic education in fostering sustainable religious awareness and moderate Islamic values.